PORTABLE CRIME DETECTION: PENDETEKSI MALING PORTABEL BERBASIS ANDROID - Kamarudin Kamarudin; Wahyudi Prasatia; Ahmad Dzaky Zain; Indah Ayu Agustina (Politeknik Negeri Batam, 2020)
Crime has increased from year to year in Indonesia with a variety of types of crimes caused by various problems such as economic, social, conflict and low legal awareness. Of the most prominent crimes in daily life are theft cases, both motor vehicle theft and theft of violence that make people feel afraid and uncomfortable in their activities. To reduce the sense of public discomfort in dealing with these cases. Portable Crime’s Detection is a portable device product that can detect thieves with an Android based. This product has two sides, namely portable devices that will be placed on objects and mobile / smartphone applications. This portable device is supported by GPS technology, technology that can track the location or existence of an object. This product is equipped with a vibration / vibration detection system so that users can be aware of interference from objects on portable devices. The internet has an important role in this product to report every activity that occurs on a portable device when needed. The device will send notifications or notifications to the user's smartphone application so users can track.